Evaluation of Waiting Time for Compounding Prescription Services at Tasik Farma Pharmacy, Tasikmalaya - Daliah, Santi Riyanti; Nugraha, Davit; Aqidah, Erni Salimatul (Ad-Dawaa : Journal of Pharmacy, 2025)
Waiting time is the time that patients can be used by patients to wait in line to get health care facilities, either at the hospital or at the pharmacy. This is related to the standard of health services that provide quality and quality. Most of the services concluded are for healing the disease. Not only for healing the patient, but also providing satisfaction with good service to the patient, so that the patient not only gets healing from his illness, but also gets good service. According to the Minister of Health Regulation No. 73 of 2016 concerning the standards of pharmaceutical services in pharmacies, the waiting time for prescription services at the pharmacy is 15-30 minutes, which is explained in article 5, page 6, paragraph 1. The purpose of the study was to determine how long the waiting time is required by the pharmaceutical personnel at the Tasik Farma pharmacy in the service of making compounded prescriptions. The method of this study uses case analysis or problems that occur with the aim of understanding and knowing the problems in depth that occur with the incoming data prescriptions.